1991
DOI: 10.1080/00365519109091624
|View full text |Cite
|
Sign up to set email alerts
|

A single plasma sample method for estimation of the glomerular filtration rate in infants and children using iohexol, I: establishment of a body weight-related formula for the distribution volume of iohexol

Abstract: This study was performed in order to develop a method for estimation of the glomerular filtration rate (GFR) from a single plasma sample based upon the plasma disappearance rate of the non-ionic contrast medium iohexol. The apparent distribution volume for iohexol was measured in 100 infants and children and used for establishment of a weight-related empirical formula for the distribution volume. Using the distribution volume obtained by this formula, a preliminary GFR was calculated from the iodine concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…The standard sampling time recommended by the British Nuclear Medicine Society when determining single sample clearance using nuclear medicine markers is 180–240 minutes . Other human studies have reported an optimal sampling time of 180 minutes . It is recommended, however, that in patients with a very low GFR, the sampling time is delayed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard sampling time recommended by the British Nuclear Medicine Society when determining single sample clearance using nuclear medicine markers is 180–240 minutes . Other human studies have reported an optimal sampling time of 180 minutes . It is recommended, however, that in patients with a very low GFR, the sampling time is delayed.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction formula for ECFV derived in this study was not found to provide a particularly accurate prediction based on the results of the agreement analysis. However, several human studies have shown that an error of up to 50% in the prediction of ECFV will not result in significant error in the clearance estimation if the timing of the sample collection is appropriate . Errors of the magnitude that may be expected to be encountered when calculating single‐sample clearance using ECFV Predicted would not be so great as to be considered clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacokinetic data regarding contrast media in children is limited [3,7]. However, the pharmacokinetic pro- files of several iodinated radiographic contrast agents are well described in adults [5,9,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…GFR was normalized to 1.73 m 2 body surface area (BSA) by the ratio 1.73/BSA, using the formula of Haycock et al [ 25 ]. The GFR1p was calculated with six different formulas: the Fleming formula [ 22 ], the Ham and Piepsz formula (Ham&Piepsz; [ 26 ], the Stake formula [ 13 , 21 ], the Groth and Aasted formula (Groth&Aasted; [ 20 ]), the Jacobsson formula [ 12 ] and a modification of Jacobsson’s formula (GFR1p-Jacobsson-mod.) [ 14 , 17 ] which is based on performing only the first step in Jacobsson’s three-step GFR calculation.…”
Section: Methodsmentioning
confidence: 99%
“…2 Plot of estimation error versus time point for glomerular filtration rate (GFR) calculated at five time points, stratified by estimation method ( n = 96 children). The y -axis shows the difference between the single-point GFR [ 12 , 13 , 17 , 20 , 22 , 26 ] and a reference GFR based on seven sampling time points. Each point corresponds to a combination of patient, estimation method and sample time.…”
Section: Methodsmentioning
confidence: 99%